Structural brain correlates in major depression, anxiety disorders and post-traumatic stress disorder: A voxel-based morphometry meta-analysis. (October 2021) - Serra-Blasco, Maria; Radua, Joaquim; Soriano-Mas, Carles; Gómez-Benlloch, Alba; Porta-Casteràs, Daniel; Carulla-Roig, Marta; Albajes-Eizagirre, Anton; Arnone, Danilo; Klauser, Paul; Canales-Rodríguez, Eric J.; Hilbert, Kevin; Wise, Toby; et al.
Highlights: MDD participants have smaller GMV than HC in cerebellum and the frontal operculum. ANX participants have less GMV than HC in temporal gyrus and pars orbitalis. PTSD participants have smaller GMV in lingual gyrus and superior frontal gyrus. As patients age, GMV reductions are more pronounced in fronto-temporal regions. Higher proportion of females are related with GMV diminutions in temporal areas. Abstract: The high comorbidity of Major Depressive Disorder (MDD), Anxiety Disorders (ANX), and Posttraumatic Stress Disorder (PTSD) has hindered the study of their structural neural correlates. The authors analyzed specific and common grey matter volume (GMV) characteristics by comparing them with healthy controls (HC). The meta-analysis of voxel-based morphometry (VBM) studies showed unique GMV diminutions for each disorder (p < 0.05, corrected) and less robust smaller GMV across diagnostics (p < 0.01, uncorrected). Pairwise comparison between the disorders showed GMV differences in MDD versus ANX and in ANX versus PTSD. These results endorse the hypothesis that unique clinical features characterizing MDD, ANX, and PTSD are also reflected by disorder specific GMV correlates.